Iconology, neoplatonism, and the arts in the Renaissance
1 online resource (xi, 234 pages)
Keywords: "The mid-twentieth century saw a change in paradigms of art history: iconology. The main claim of this novel trend in art history was that renown Renaissance artists (such as Botticelli, Leonardo or Michelangelo) created imaginative syntheses between their art and contemporary cosmology, philosophy, theology and magic. The Neo-Platonism in the books by Marsilio Ficino and Giovanni Pico della Mirandola became widely acknowledged for their lasting influence on art. It thus became common knowledge that Renaissance artists were not exclusively concerned with problems intrinsic to their work, but that their artifacts encompassed a much larger intellectual and cultural horizon. This volume brings together historians - both those concerned with the history of their own discipline and also those whose research is on the art and culture of the Italian Renaissance itself - with historians from a wide variety of specialist fields, in order to engage with the contested field of iconology. The book will be of interest to scholars working in art history, Renaissance history, Renaissance studies, historiography, philosophy, theology, gender studies, and literature"--